Education in fostering a united and caring citizenship in Malaysia - Hashim, Rosnani (Prentice Hall, Pearson Education South Asia Pte. Ltd., 2007)
Multiculturalism is on the rise in even typically homogeneous nations such as the European countries and Japan. This new cultural diversity that has developed in the local arena poses a new problem of national unity and identity. As each ethnic group desires to maintain its culture, religion and language, it poses a problem for the central government which would like to see the use of a common language and its citizens being united and sharing a common destiny. The diversity of culture, ethnicity, race and language, especially when any of these variables is used to provide special privileges to some groups and deny others equal opportunities to participate, will create tension, instability, upheaval, racial polarisation and conflict (Hashim, 2005). The challenges of multiculturalism in democratic education have been raised by Gutmann (1995) who argued that integrating the aims of cultivating a concern for human beings alongside a sense of civic responsibility, and coping with the conflicts between them, is the most fonnidable challenge for the philosophy and practice of democratic education